Performance Evaluation of Internet of Things Prototype for Preeclampsia Monitoring in Antenatal Care - Musyoka, Faith M. (My University, 2020)
Globally, Preeclampsia has been an alarming condition, thus creating a major concern in its prevention and monitoring. Software developers have implemented several Internet of Things systems to transform human society towards becoming convenient and efficient with maternal health benefits. Due to the freedom in developing these systems, evaluation of the systems’ performance must be addressed to enable this revolutionized transformation. Therefore, the study selected an already developed 24-hour ambulatory blood pressure monitoring system for preeclampsia management in antenatal care to represent other IoT systems in conducting the performance evaluation. A sample of fifty pregnant mothers was selected using purposive and simple random sampling to conduct the performance evaluation. The study used a total of 200 blood pressure readings from pregnant mothers. Consistency, response rate, accuracy, reliability, and output were the metrics used to evaluate the IoT based system’s performance. During performance evaluation, the study found out that the system achieved all the functionalities expected in its assessment. Therefore, the IoT based system has the potential to inform future antenatal practices.
Keywords: Antenatal care; Internet of Things (IoT); Performance Evaluation; Preeclampsia